Somatization symptoms and burnout: a correlational study among emergency nurses - Li, Ningxiang; Xie, Nan; Chen, Xiaoli; Zhang, Hao; Zhong, Luying; Diao, Dongmei; Zhu, Ling; Zhou, Yue (Frontiers in Public Health, 2025)
BackgroundSomatic symptom disorder is influenced by various factors, with increasing evidence highlighting its close association with burnout. This study aimed to investigate the correlation between somatization symptoms and burnout levels among emergency nurses, focusing on the impact of burnout on somatization.MethodsA cross-sectional study was conducted involving 1,540 emergency nurses working in tertiary hospitals in China. Data collection occurred between December 26, 2023, and January 18, 2024, using the Chinese versions of the Maslach burnout inventory–general survey (MBI-GS) and the somatic symptom disorder self-rating scale (SSD-CN). Statistical analyses were performed using SPSS version 25.0.ResultsThe mean SSD score was 39.58 ± 13.61, with 53.4% of participants exhibiting moderate to severe somatization symptoms. The mean burnout score was 4.77 ± 6.16, with a burnout incidence of 57.3%. A positive correlation was identified between the composite burnout score and the total SSD score (Pearson correlation coefficient = 0.534, p < 0.01). Emotional exhaustion and depersonalization scores were also positively correlated with individual SSD domain scores and the total SSD score (p < 0.01), Multivariate linear regression analysis revealed significant factors influencing somatization symptoms, including 6–10 and 11–15 years of work experience, weekly working hours of 41–48 or 49–58, 5–8 or >9 night shifts per week, monthly incomes ≥10,000 RMB and the composite burnout score (p < 0.05).ConclusionEmergency nurses in this study exhibited severe somatization symptoms, with burnout identified as a significant contributing factor. To address this issue, healthcare management should consider implementing alternative shift patterns, optimizing workforce allocation, and revising compensation systems to ensure equitable labor distribution. These measures would support the healthy development of emergency nurses. Furthermore, nurses should prioritize self-care by engaging in activities such as psychological interventions, positive thinking training, and yoga to reduce burnout and enhance overall health.